The Status quo and Problem of User Well-Being Related to Standard Design School Buildings: A Case Study of Primary School Buildings, Mueang District and Area, Nakhon Ratchasima Province - Rattanapradab , Pattamaporn; Chaiyakul, Yingsawad (Journal of Architectural/Planning Research and Studies (JARS), 2022)
A building’s environment is a major factor affecting the well-being of its users. Health conditions of a school building’s users are related to several factors including location, physical appearance, and environment. This article presents an assessment of the current state of school buildings which were constructed in accordance with an approved standard design under the Ministry of Education in the area of Mueang District, Nakhon Ratchasima Province. Four standard designs of school buildings that have been highest constructed in the studied area were selected consisting of 8 buildings located in 6 schools. First, it was found that the Location of school buildings affected the conditions of noise and ventilation. School buildings located in urban areas, near main roads, and in areas of high–density communities, have a higher level of background noise than those in suburban areas. School buildings in suburban areas, and those located in agricultural zones with more open spaces than the urban ones, The maximum average wind speed is 0.48 m/s in the open space. There are no obscured buildings, resulting in school buildings not being able to operate openings because of the high wind speed. Secondly, in relation to Appearance there was an extension or adjustment of some areas for other functions that differed from the standard building design in 7 buildings, while one building was completely unused. Buildings currently in use have room–sizes and voids that support light and natural ventilation, while construction materials of these buildings do not have proper noise protection and absorption properties. Thirdly, with respect to Environment, standard measurements were taken in 23 classrooms from the sample school buildings, in both in Mueang District and suburban areas nearby, with high levels of background noise (35 dBA) being recorded; lower brightness (natural and artificial light) than the standard criteria (300 lx) was recorded in 3 classrooms, while 5 other classrooms exceeded the standard, with recorded values of 318 - 939 lx. Excessive brightness from the sunlight may have detrimental effects on visual comfort and thermal comfort of users from glare and burdened heat respectively. Moreover, one school building in the suburban area had 3 classrooms that were outside of a thermal comfort zone; measuring its average high temperature. A bioclimatic chart-based analysis of comfortable conditions found that three classrooms in Building C1 were outside the comfort zone, with the highest temperature in the afternoon (01:00 - 4:00 pm) being 31.2°C. Relative humidity 33.7%. Therefore, it can be concluded that the impacts on user well-being related to school building design and construction were noise, brightness and thermal comfort zone, respectively.